Travel Mode Choice for Domestic Intercity Travel: A Case Study in Suzhou, China - Qi Deng; Isaac Henderson (ASEAN Journal on Hospitality and Tourism, 2022)
This study examines how residents in Suzhou, China choose between different travel modes for domestic intercity travel. Suzhou provides an interesting case study because of its developed high-speed rail (HSR) network and proximity to three major airports. Semi-structured qualitative interviews were administered to 158 participants to obtain information about their most recent intercity trip and important factors for choosing travel modes. The interviews were thematically analysed, and participants were coded as being in or out of themes to allow for chi-squared tests of independence (to examine associations between themes and demographic variables) and binary logistic regressions (to predict travel mode choice based upon themes). The findings show that accessibility, convenience, and price increase the likelihood of a participant having chosen HSR. However, the more important contribution is methodological, highlighting the importance of studying actual behaviours (rather than attitudes and preferences) and avoiding the issues of self-generated validity and construct creation.